2017
DOI: 10.1007/s10792-017-0500-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of macular and peripapillary choroidal thickness, macular volume and retinal nerve fiber layer in acromegaly patients

Abstract: The macular and peripapillary choroidal thickness, retinal nerve fiber layer, and total retinal volume of the macula were significantly higher in acromegaly patients. Increased choroidal thickness may cause different macular pathologies such as choroidal neovascularization. RNFL results may be important in acromegaly patients with glaucoma, especially if the progress of glaucoma is monitored by OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
5
0
1
Order By: Relevance
“…In ocular tissues, growth in extraocular muscles [3], increase in intraocular pressure (IOP) [4], and increase in corneal thickness [5] have been shown previously. Also retinal thickness increase [6], increase in choroidal thickness [7], ganglion cell complex (GCC) thickness reduction [8][9][10][11][12], retinal nerve fibre layer (RNFL) thickness increase [6]/ decrease [4,12], and increase in the incidence of proliferative retinopathy [13] have been shown previously by using optic coherence tomography (OCT) and fundus fluorescein angiography.…”
Section: Introductionmentioning
confidence: 80%
“…In ocular tissues, growth in extraocular muscles [3], increase in intraocular pressure (IOP) [4], and increase in corneal thickness [5] have been shown previously. Also retinal thickness increase [6], increase in choroidal thickness [7], ganglion cell complex (GCC) thickness reduction [8][9][10][11][12], retinal nerve fibre layer (RNFL) thickness increase [6]/ decrease [4,12], and increase in the incidence of proliferative retinopathy [13] have been shown previously by using optic coherence tomography (OCT) and fundus fluorescein angiography.…”
Section: Introductionmentioning
confidence: 80%
“… 24 On the other hand, subfoveal choroidal thickness and foveal thickness were increased in patients with controlled acromegaly. 49 Moreover, Yazgan et el 37 showed positive correlation between macular choroidal thickness and serum IGF1 level. In turn, Polat et al 50 revealed no significant difference in mean central retinal thickness between the patients with acromegaly and the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports also disclosed that there is a correlation between systemic level of IGFs and the changes in eye structures. 36 , 37 The abovementioned studies suggested that the source of elevated level of IGF family in ocular diseases still needs explanation. Moreover, there was revealed a significant correlation between serum and vitreous level of VEGF in proliferative diabetic retinopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subfoveal and peripapillary CT did not differ significantly between shunted patients and healthy controls. Yazgan et al ( 103 ) reported that patients with acromegaly had significantly higher macular and peripapillary CT than healthy controls. Garcia-Martin et al ( 104 ) reported that the peripapillary choroid was significantly thicker in patients with Parkinson's disease than in age- and sex-matched controls.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 99%